Khyber Pakhtunkhwa and Federally Administered Tribal Areas : Post-crisis Needs Assessment - Asian Development Bank (World Bank, Washington, DC, 2013)
Years of regional instability underpinned by decades of poor governance have shaped the crisis unraveling in the north western border areas of Pakistan. Marginalization and inequity are sustained in the Federally Administered Tribal Area (FATA) through current legislation, and in both FATA and Khyber-Pakhtunkhwa (KP) province by underdevelopment. The life saving humanitarian, recovery and longer-term development efforts of the federal and provincial governments, the military, humanitarian agencies, donors and international financial institutions (IFIs) continue to be enormously necessary, but not sufficient to transform the situation and reverse the support for violent change. To assist in tackling this, the Government of Pakistan requested support with the preparation of a Post-Crisis Needs Assessment (PCNA) resulting in a peace building strategy for FATA and KP. The goal of the PCNA is to produce a helpful, programmatic, coherent and sequenced peace building strategy for the Government of Pakistan that delivers the agreed vision within ten years.